Crystal structure of a closed ternary complex of a HNA Reverse Transcriptase in complex with a HNA/DNA duplex - Cédric Gutfreund; Mikhail Abramov; Frédérick Coosemans; Philipp Holliger; Piet Herdewijn; Karin Betz; Andreas Marx (PLoS ONE, 2026)
1,5-Anhydrohexitol nucleic acid (HNA) is a promising xeno nucleic acid (XNA) for applications such as aptamers and catalysts, due to its favourable physico-chemical properties. Realizing this potential requires efficient and high-fidelity polymerases capable of processing HNA. A key component are HNA reverse transcriptases that convert HNA into DNA, an essential step in standard SELEX workflows. Although HNA reverse transcriptases have been generated by directed evolution, structural insight is essential to guide further enzyme engineering. Here, we report the 2.8 Å crystal structure of the engineered HNA reverse transcriptase KOD-H4, derived from the B-family DNA polymerase of Thermococcus kodakarensis , captured in a closed ternary complex with dATP, a 3’-terminated primer and a mixed HNA/DNA template. Compared to a previously reported open ternary KOD-H4 structure, the presented structure adopts a more closed conformation with increased finger and thumb domain closure and formation of a canonical Watson–Crick–Franklin base pair at the insertion site. Direct downstream nucleotides show more distorted base pairing and one HNA residue transits from the unusual 1 C 4 conformation it adopted in the open complex to the 4 C 1 hexitol sugar conformation. These findings demonstrate that KOD-H4 can form a closed, pre-catalytic complex resembling that of the wildtype enzyme with natural substrates, and reveal state-dependent conformational flexibility of HNA. Such flexibility should be considered in the design and optimization of enzymes that process HNA.